2022
DOI: 10.1364/oe.449860
|View full text |Cite
|
Sign up to set email alerts
|

Optical camera communication (OCC) using a laser-diode coupled optical-diffusing fiber (ODF) and rolling shutter image sensor

Abstract: We demonstrate an optical-camera-communication (OCC) system utilizing a laser-diode (LD) coupled optical-diffusing-fiber (ODF) transmitter (Tx) and rolling-shutter based image sensor receiver (Rx). The ODF is a glass optical fiber produced for decorative lighting or embedded into small areas where bulky optical sources cannot fit. Besides, decoding the high data rate rolling-shutter pattern from the thin ODF Tx is very challenging. Here, we propose and experimentally demonstrate the pixel-row-per-bit based neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…On the other hand, in scenarios where the signal-to-noise ratio (SNR) is not high and ZF equalisers are limited, MMSE equalisers would be more suitable. Equation (5) shows the calculation of the matrix that is used to approximate the received signal to the transmitted signal.…”
Section: Multispectral Camera Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in scenarios where the signal-to-noise ratio (SNR) is not high and ZF equalisers are limited, MMSE equalisers would be more suitable. Equation (5) shows the calculation of the matrix that is used to approximate the received signal to the transmitted signal.…”
Section: Multispectral Camera Communicationmentioning
confidence: 99%
“…Furthermore, Tsai et al proposed a pixelrow-per-bit-based neural network to decode data produced by an optical-diffusing-fibre (ODF) transmitter in an OCC link. The authors demonstrated that the proposed algorithm enhanced the BER compared to traditional artificial neural network (ANN) [5].…”
mentioning
confidence: 99%
“…By using decision feedback equalization (DFE) with 40 feed-forward and 20 feed-backwards taps, the intersymbol interference (ISI) of the on-off-keying (OOK) signal was mitigated, achieving 1.1 Gbit/s operation. In 2022, Tsai et al proposed and illustrated a 360 o wide FOV optical camera communication (OCC) system using a phosphor-coated light diffusing fiber [41]. When blue laser diode (LD) was coupled at one end of the light diffusing fiber, blue light was scattered and emitted at the fiber circumference.…”
Section: Introductionmentioning
confidence: 99%
“…By using decision feedback equalization (DFE) with 40 feed-forward and 20 feed-backward taps, the intersymbol interference (ISI) of the on-off-keying (OOK) signal was mitigated, achieving 1.1 Gbit/s operation. In 2022, Tsai et al proposed and illustrated a 360° wide FOV optical camera communication (OCC) system using a phosphor-coated light diffusing fiber [ 41 ]. When a blue laser diode (LD) was coupled at one end of the light-diffusing fiber, blue light was scattered and emitted at the fiber circumference.…”
Section: Introductionmentioning
confidence: 99%
“…The LDOF used here is the same as that in ref. [ 41 ]; however, ref. [ 41 ] is based on rolling shutter-based OCC.…”
Section: Introductionmentioning
confidence: 99%